Improving Student Learning Outcomes Through the Inquiry Method on Visual Journal Material in Arts and Culture Subjects in Class X E.9 of SMA Negeri 1 Padang - Azizah, Fitriah; Astuti, Fuji; Andrizal, Andrizal; Ardipal, Ardipal (Universitas Pahlawan Tuanku Tambusai, 2026)
Student learning outcomes in the visual journal material of the Arts and Culture subject in class X E.9 SMA Negeri 1 Padang are still low due to the teacher-centered approach that limits active student involvement. This study aims to examine the effectiveness of the inquiry method to improve student learning outcomes. This type of research uses Classroom Action Research (CAR) with the Kemmis and McTaggart model in two cycles. The population and sample consisted of 36 students of class X E.9. Instruments include learning outcome tests, observation sheets, questionnaires, and documentation, analyzed descriptively quantitatively using SPSS and qualitatively through triangulation. The results show an increase in the average value from 74.28 (pretest) to 80.81 (cycle I) and 89.44 (cycle II), with a standard deviation decreasing from 3.62 to 2.47. Observations recorded a significant increase in student activity. The study concluded that the inquiry method is effective in improving learning outcomes and student involvement in visual journal learning.